ОСОБЛИВОСТІ ВИРАЖЕННЯ КАТЕГОРІЇ ВИДУ В ІТАЛІЙСЬКІЙ МОВІ - Червона, О.С. (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching)
Цю статтю присвячено дослідженню категорії виду та особливостям її вираження в італійській мові. Були розглянуті теоретичні засади щодо вивчення категорії виду у романських мовах, а саме в італійській, та детермінативи, за допомогою яких, може модифікуватися лексичний характер італійського дієслова. Ключові слова: детермінатив, дієслівний перифраз, італійське дієслово, категорія виду, опозиція форм. Червона О.С. Особенности выражения категории вида в итальянском языке. Эта статья посвящена изучению категории вида и особенностям её выражения в итальянском языке. Были рассмотрены теоретические основы изучения категории вида в романских языках, а именно в итальянском, и детерминативы, с помощью которых может видоизменяться лексический характер итальянского глагола. Ключевые слова: детерминатив, глагольный перифраз, итальянский глагол, категория вида, оппозиция форм. Chervona O. Characteristics of the category of aspect in Italian. This article focuses on the category of aspect and its characteristics in Italian. The theoretical principles have been investigated in relation to the studies of the category of aspect in Roman languages namely Italian and determinatives with the help of which may be modified the lexical character of Italian verb. Key words: determinative, verbal periphrasis, Italian verb, category of aspect, opposition of forms.